Susceptibility‐induced distortion correction in hyperpolarized echo planar imaging - Miller, JJ; Lau, AZ; Tyler, DJ (Wiley, 2017)
Purpose Echo planar imaging is an attractive rapid imaging readout that can image hyperpolarized compounds in vivo. By alternating the sign of the phase encoding gradient waveform, spatial offsets arising from uncertain frequency shifts can be determined. We show here that blip-reversed echo planar imaging can also be used to correct for susceptibility and B0 inhomogeneity effects that would otherwise produce image-domain distortion in the heart. Methods Previously acquired blip-reversed cardiac 3D-Spectral-Spatial echo planar imaging volumetric timecourses of hyperpolarized [1-13C]pyruvate were distortion corrected by a deformation field estimated by reconstructing signal-to-noise ratio (SNR)-weighted progressively subsampled temporally summed images of each metabolite. Results Reconstructing blip-reversed data as proposed produced volumetric timecourses that overlaid with proton reference images more consistently than without such corrections. Conclusion The method proposed may form an attractive method to correct for image-domain distortions in hyperpolarized echo planar imaging experiments. Magn Reson Med, 2017. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.